Kreativitas Guru Dalam Mengembangkan Sikap Percaya Diri Pada Siswa Dalam Pembelajaran Al Qur’an Di Madrasah Diniyah Awaliyah Nurul Ikhlas Jorong V Pertemuan Kabupaten Pasaman - Kasrianto Kasrianto; Iswantir M; Arifmiboy Arifmiboy; Charles Charles (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This research is motivated by phenomena or symptoms from the author's observations about teacher creativity in developing students' self-confidence in learning the Koran at Madrasah Diniyah Awaliyah (MDA) Nurul IKhlas Jorong V Meeting, that many students in learning the Koran are not confident and even when reading the Koran many students are nervous and even many make mistakes in reading the Koran, this happens because students' confidence in learning the Koran is still minimal. This research is a field research (field research) which is descriptive qualitative. The data collection used during this research was by using data collection techniques through interviews and observation. This study uses key informants and supporting informants. The key informant in this study was 1 person, namely the teacher learning the Koran while for the supporting informants, namely class IV MDA Al Ikhlas, then the authors conducted a descriptive analysis with data reduction and to test the validity of the data in this study the authors used data triangulation. Based on the results of the study it can be understood that the Al-Quran teacher at MDA Al Ikhlas is already creative when teaching in class so that the self-confidence of the students increases.